Financial law and its scientific evolution in the Revista de Ciencias Juridicas at the University of Costa Rica: 60 years of development - Jiménez Zeledón, Mariano (2026)
This paper aims to review the concept of financial law and its classifications (public budget law, tax law, public credit law), to then review the articles on these matters during the 60 years of scientific law magazine publications, formulating conclusions of this development in relation to tax law at the Law School of the University of Costa Rica.